Timing-Sound Interactions: Groove-Forming Elements in Traditional Scandinavian Fiddle Music - Johansson, Mats (Puls – musik- och dansetnologisk tidskrift, 2022)
This article reports on a study of concepts and practices of microrhythm among skilled performers of traditional Scandinavian fiddle music, particularly the so-called springar tradition which features non-isochronous and variable beats and subdivisions within a triple meter framework. In this context, microrhythm refers to the overall shaping of musical events at the micro level, encompassing both timing (temporal placement and duration) and sound (shape/envelope, timbre and intensity). A particular focus is to explore how these musical features interact – as opposed to treating timing and sound separately – and how timing-sound interactions in turn are understood in terms of groove-forming elements. The study consisted of semi-structured interviews with four expert musicians, which have been transcribed and coded for key themes and concepts. Subsequently, these data were complemented by analyses of relevant musical segments. The interviews focused on the defining features of a good groove, and how aspects of sound are envisaged to affect aspects of rhythm and timing, and vice versa. It was found that groove is largely conceptualised in terms of movement and embodiment; that musical features (timing, accentuation, ornamentation, tone production) are seen to interact and overlap, suggesting a multi-parametrical concept of groove; and that melodic-rhythmic variation is an important groove-forming element. The interviews also revealed a strongly practice-oriented perspective on performance and aesthetics in which musical concepts are tightly integrated with their associated sound-producing movements (bowing, fingering, foot tapping).